2000
DOI: 10.1046/j.1537-2995.2000.40070875.x
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus type C/HGV markers in HCV RNA‐positive French blood donors: correlation with HCV genotypes and risk factors

Abstract: In persons with HCV infection, IV drug use seems to be a major route of GBV-C/HGV transmission. Precautions taken to avoid HCV infection will probably also decrease GBV-C/HGV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Also, in Thailand the GBV-C RNA positivity among blood donors was 4.8% [51]. In France, among 306 HCV RNA-positive donors, 19.3% were GBV-C RNA positive [52]. In Egypt, El-Zayadi et al, [53] found 12.2% of GBV-C prevalence among blood donors and GBV-C coinfection in HBV and HCV infected patients were 7.6 and 64.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in Thailand the GBV-C RNA positivity among blood donors was 4.8% [51]. In France, among 306 HCV RNA-positive donors, 19.3% were GBV-C RNA positive [52]. In Egypt, El-Zayadi et al, [53] found 12.2% of GBV-C prevalence among blood donors and GBV-C coinfection in HBV and HCV infected patients were 7.6 and 64.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%